Nasoalveolar molding of malpositioned and protruding premaxillary segment in a neonatal case of bilateral cleft lip and palate - Lucky Yadav; Navraj Mattu; Rakesh Sharma; S S Karthickeyan (Wolters Kluwer Medknow Publications, 2024)
This report discusses bilateral complete cleft lip and palate (BCLP) and the efficacy of presurgical infant orthopaedics, particularly nasoalveolar molding (NAM). NAM involves custom appliances to reduce cleft severity before primary surgery. A case report illustrates successful NAM treatment in a 2-day-old female with Veau type IV cleft lip and palate. The method aligns alveoli, lip, and nose, improving surgical outcomes and minimizing scar tissue. NAM has shown unique benefits, making it a preferred treatment in BCLP cases for better patient care. The technique aims to reduce the severity of the cleft deformity, leading to improved nasal appearance.